Prosedur Pemberhentian Presiden atau Wakil Presiden dalam Masa Jabatannya Menurut Sistem Ketatanegaraan Republik Indonesia - Ave Maria Stela Mali; Kotan Y. Stefanus; Hernimus Ratu Udju (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The Unitary State of the Republic of Indonesia is a unitary state in the form of a Republic, where the Head of State and Head of Government is the President and assisted by a Vice President in carrying out his duties. The term of office of the President and Vice President according to the 1945 Constitution is 5 years and can be re-elected in the next period. The President and/or Vice President may be dismissed during their term of office for various reasons. This research is a normative juridical research, namely, research conducted by reading works related to the procedure for the dismissal of the President and/or Vice President and the implications of the dismissal of the president and/or deputy in his term of office according to the constitutional system of the Republic of Indonesia. The results of this study show that: (1) The procedure for the dismissal of the President and/or Vice President during their term of office before the amendment of the 1945 Constitution has not been regulated in a limitative manner. Prior to the amendment, the MPR was the highest state institution that had the authority to dismiss the President and/or Vice President during his term of office. After the amendment of the 1945 Constitution, the procedure for dismissing the President and/or Vice President during his term of office has been regulated in Article 7B of the 1945 Constitution. (2) The dismissal of the President and/or Vice President during his term of office has implications for the continuation of the government and the life of the community in the future.